Modernist cuisine : the art and science of cooking - Myhrvold, Nathan, 1959- (The Cooking Lab, 2011)
"An overview of the techniques of modern gastronomy. Nathan Myhrvold, Chris Young, and Maxime Bilet -- scientists, inventors, and accomplished cooks in their own right -- have created a six-volume 2,400 page set that reveals science-inspired techniques for preparing food. The authors and their 20 person team at The Cooking Lab have achieved new flavors and textures by using tools such as water baths, homogenizers, centrifuges, and ingredients such as hydrocolloids, emulsifiers, and enzymes."--Resumé vydavatele
Svazky 1-5 jsou vázané (34 cm), svazek 6 je v kroužkové vazbě (28 cm)
Terminologické slovníky ve svazku 5
Keywords: gastronomie; příprava jídel; kuchařství; potraviny; gastronomy; meals preparation; cookery; foodstuffs; příručky; kuchařské recepty; handbooks and manuals; cookbooks